Targeted terapy against angiogenesis in renal cell carcinoma - Obrocka, Beata; Wcisło, Gabriel; Korniluk, Jan; Szarlej-Wcisło, Katarzyna; Nurzyński, Paweł; Duchnowska, Renata; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Renal cell carcinoma (RCC) represents 3% of all cancers diagnosed in Poland, and morbidity: 5/100 000, and 2. 8/100000 for male and female, respectively. One of the well-know prognostic factors is neo-angiogenic activity of a tumor. The parameter which is associated with this activity is microvessel density (MVD). High MVD is a poor prognostic factor for RCC patients even at early stages (T1 and T2). In contrary, low MVD significantly improved survival of patients with organ-confined RCC. Moreover, low MVD has proved to be a good independent predictive factor on multivariate analysis. Overexpression of well- characterized proangiogenic factors such as: VEGF, bFGF, TGF-B1, their correlated with high MVD and the poor prognosis. For instance, in vivo experimental systems showed that increased expression of the proangiogenic cytokines as e.g. bFGF, increased the number of metastases to the lymph nodes or liver greater than 10-fold. Although, one of the most well-characterized proangiogenic factors appeared to be VEGF. Increased levels of this molecule have been found in most hypervascular RCC. Moreover, antibodies against VEGF had influence on tumor vasculature by blocking the angiogenic activity. Tumors expressing all three isoforms of VEGF (121,165, 189 amino acids nymbers) are more vascular and this phenomenon correlates with advanced disease. Angiogenesis remains to fight as the target for improving the results of therapeutic setting in kidney cancer. It is a long list of antiangiogenic substances that, probably, will take place in a therapy of renal cell carcinoma. Some of the substances as: IL-12, angiostatin, endostatin, TNP-470, Vit-D analogs, Captopril have been characterized, although, the list is growing rapidly. Immunotherapy with monoclonal antibodies against VEGF is still moot. Interferon - alpha is now used as the standard drug in the therapy of advanced RCC and response rate is expected between 15-and 20%. Although, the mechanisms of its activity are still unknown. However combaining interferon-alpha with other substances, e.g. 13-cis retinoid acid, gives a better chance to obtain 30% overall response rate. Antiangiogenic therapy in case of RCC is a fledgling idea. Therefore, meticulous testing of novel substances is necessary to generate better drugs in RCC. Yet physicians must wait to improve results in order to accept this novel setting as the standard or additional modality in the therapy of RCC.